Uji Efektivitas Sedian Salep Daun Mangga Arumanis (Magnifera Indical L.) Terhadap Luka Sayat Mencit Putih (Mus musculus) Jantan Yang Diinduksi Aloksan - Yerly Ramadani Lubis; Astriani Natalia Br Ginting; Roy Indrianto Bangar (Journal of Pharmaceutical and Sciences, 2026)
Background: Diabetes mellitus is a major risk factor for impaired wound healing. Conventional treatments are often expensive and carry a risk of side effects, necessitating the development of safe and effective topical therapy alternatives from natural ingredients. Arumanis mango leaves (Mangifera indica L.) are reported to contain bioactive compounds such as mangiferin and flavonoids, which have potential in the tissue regeneration process. Objective: To determine the effectiveness of an arumanis mango leaf extract ointment on the healing of incision wounds in male mice with alloxan-induced diabetes. Methods: This laboratory experimental study used 30 male BALB/c mice divided into 6 groups: normal, diabetic without treatment, diabetic with base ointment, and three diabetic groups treated with mango leaf extract ointment (concentrations of 5%, 10%, 15%). Diabetes was induced via intraperitoneal alloxan injection. Aseptic incision wounds were created on the mice's backs and topically treated with the ointment once daily for 14 days. Wound diameter and blood glucose levels were measured periodically. Data were analyzed statistically. Results: Groups treated with mango leaf extract ointment (10% and 15% concentrations) showed faster and complete wound healing (100%) by day 14, which was not significantly different from the normal group and was markedly better than the untreated diabetic group (39%). However, no significant reduction in blood glucose levels was observed in any diabetic group throughout the study. Conclusion: The arumanis mango leaf extract ointment is effective topically in accelerating incision wound healing in diabetic mice, without demonstrating systemic antihyperglycemic effects. This effect is presumed to be mediated by bioactive compounds acting locally at the wound site.